PENINGKATAN PENGGUNAAN ANTIBIOTIK BIJAK MELALUI DETEKSI DINI MRSA PADA POSDAYA SUNAN KALIJAGA, BERKOH, PURWOKERTO - Dwi Utami Anjarwati; Rahmawati Wulan Sari; Rani Afifah Nur Hestiyani (Universitas Jenderal Soedirman, 2020)
The use of antibiotics that is not wise can cause an increase in the incidence of antibiotic resistance in the community. This community service aims to conduct early detection (screening) MRSA as an effort to increase knowledge and increase public awareness in the wise use of antibiotics. The method used in community service was the identification of MRSA from the smeared nose and throat of the members of Posdaya Sunan Kalijaga, RW 2, Berkoh, Purwokerto. Antibiotic susceptibility test performed by using the disc diffusion method, Kirby Bauer. History of antibiotic use in the community is obtained by using a questionnaire. The results of this activity show that S.aureus bacteria found in the community are still sensitive to cefoxitin, Staphylococcus aureus proportion was 9.33% of nasal smear and 34.66% of throat smear. However, the use of antibiotics that is not wise is still found in the community as much as 17.33%. The results of the activity were informed to the public as a reference to improve antibiotic use wisely.Keywords: Antibiotic Resistance, Staphylococuss aureus, MSSA, MRSA